2013
DOI: 10.1016/j.physbeh.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

State anxiety and cortisol reactivity to skydiving in novice versus experienced skydivers

Abstract: Previous studies have suggested that skydiving, a naturalistic stressor, is associated with increases in self-reported stress, anxiety and cortisol levels. However, it has not been established whether this stress reactivity is altered as a function of repeated exposure to skydiving. This is of interest due to previous observations that cortisol reactivity becomes habituated with repeated exposure to laboratory stressors, however, few studies have investigated such habituation to naturalistic stressors. State a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 22 publications
3
38
0
1
Order By: Relevance
“…Other studies also found a lack of concordance between the self-reported levels of anxiety and biological stress reactivity 34 , or a lack of relationship between cortisol and anxiety at certain time points of a stress paradigm. 9 Although these seem to be interrelated, anxiety and physiological stress are distinct constructs that may be individually activated under specific circumstances.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies also found a lack of concordance between the self-reported levels of anxiety and biological stress reactivity 34 , or a lack of relationship between cortisol and anxiety at certain time points of a stress paradigm. 9 Although these seem to be interrelated, anxiety and physiological stress are distinct constructs that may be individually activated under specific circumstances.…”
Section: Discussionmentioning
confidence: 98%
“…Such paradigms could include exposure to potentially life-threatening stressors, such as extreme sports (e.g. Hare et al, 2013). It would potentially be of even greater interest to better understand whether the negative associations between mood and Type D observed during the pre-stress period both in the present study, and elsewhere ) are attributable to a general reduction in basal mood in Type D individuals, or whether this reduction in pre-stress mood is specifically related to anticipation of the stressor.…”
mentioning
confidence: 99%
“…These more accurate measurements of the time domain of HRV lead us to consider the hormonal response to be responsible for these. The cortisol response is indeed significant at the time of jump but clearly peaks after the jump as pointed out by many authors (Taverniers et al 2011;Hare et al 2013;Deinzer et al 1997).…”
Section: Discussionmentioning
confidence: 64%
“…Parachute jumping is considered as a "real-world acute emotional stress" or "life-threatening" event (Mujica-Parodi et al 2009a, b;Dikecligil and Mujica-Parodi 2010) and thus commonly used as a model to assess the physiological mechanisms involved in the acute stress response (Dikecligil and Mujica-Parodi 2010; Hare et al 2013). In particular, free fall has been studied in beginners with the scope of understanding psychological rather than environmental stress (Chatterton et al 1997;Dikecligil and Mujica-Parodi 2010;Roth et al 1996;Hare et al 2013;Taverniers et al 2011;Cavenett and Nixon 2006). During parachute jumping, it seems well admitted that the steady-state response to the stress exposure is an increase in heart rate (HR) (Shane and Slinde 1968;Reid et al 1971;Schedlowski and Tewes 1992;Roth et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation